KONSEP BERPIKIR DALAM AL-QUR’AN DAN IMPLIKASINYA TERHADAP PENDIDIKAN AKHLAK - Muhammad Ismail (Ta'dib: Jurnal Pendidikan Islam, 2014)
The substance of education is knowledge transformation process. Therefore, it needs appropriate methods and media to transfer it. In Islamic education context, these methods and media seem to be education curriculum. Moreover, the objective is moral establishment. Once the education curriculum is satisfactory, it could establish ethical person. One of the important curriculum aspects is right understanding of thinking concept according to Al-Qur’an. Conceptually, thinking has a very deep meaning. It was stated in some ayahs in Al-Qur’an. Some of them stated in the terms of: tafakkur, tadzakkur, tadabbur, and ta’aqqul. Specially, those terms have their special meanings. Those meanings lead up to one concept as heart concept (Qalb). Simply, thinking concept in Al-Qur’an a thinking process that involve heart and mind in understanding knowledge. Additionally, if this concept is implemented in education, it could create good characteristic human being because heart (Islamic perspective) is the place of iman, ihsan, taqwa, ikhlas, ridha, and so on.